2023
DOI: 10.1038/s41586-022-05675-0
|View full text |Cite|
|
Sign up to set email alerts
|

Population-based heteropolymer design to mimic protein mixtures

Abstract: Biological fluids, the most complex blends, have compositions that constantly vary and cannot be molecularly defined1. Despite these uncertainties, proteins fluctuate, fold, function and evolve as programmed2–4. We propose that in addition to the known monomeric sequence requirements, protein sequences encode multi-pair interactions at the segmental level to navigate random encounters5,6; synthetic heteropolymers capable of emulating such interactions can replicate how proteins behave in biological fluids indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 47 publications
0
25
0
2
Order By: Relevance
“…While prior work has leveraged assembly protocols to bias structure formation (e.g., toward globular morphologies), here we show that dispersity outcomes (either SCNP size or nanostructural environments) might be manipulated either by setting particular precursor parameters or by tailoring sequences. Furthermore, with many demonstrations of using statistical ensembles of chains in functional materials, it will be interesting to consider how distributions of chains can be designed to achieve target properties. Approaches to navigate such design tasks, particularly in the context of experimentally verifiable systems will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…While prior work has leveraged assembly protocols to bias structure formation (e.g., toward globular morphologies), here we show that dispersity outcomes (either SCNP size or nanostructural environments) might be manipulated either by setting particular precursor parameters or by tailoring sequences. Furthermore, with many demonstrations of using statistical ensembles of chains in functional materials, it will be interesting to consider how distributions of chains can be designed to achieve target properties. Approaches to navigate such design tasks, particularly in the context of experimentally verifiable systems will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…In their latest work, random copolymer mixtures with precise monomer ratios were synthesized to carry out specific functions. [25] Here, the random copolymers proved to be capable of assisting protein folding, enhancing the thermal stability of proteins, and acting as a synthetic substitute for the cytosol. In these studies, it was shown that complex, biologically relevant functions can be conducted by random copolymers without a defined primary sequence but instead consisting of a mixture of individual polymer chains only similar in their average monomer composition.…”
Section: Protein Stabilizationmentioning
confidence: 99%
“…The random copolymers distributed themselves in the lipid bilayer, forming bilayer‐spanning segments, allowing for proton transport through the bilayer. In their latest work, random copolymer mixtures with precise monomer ratios were synthesized to carry out specific functions [25] . Here, the random copolymers proved to be capable of assisting protein folding, enhancing the thermal stability of proteins, and acting as a synthetic substitute for the cytosol.…”
Section: Folding Synthetic Polymers Into Functional Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations